THE ROLE OF ZOROASTRIANISM IN THE ANCIENT STATE OF BACTRIA - Safarali Yusupovich Kushokov (Scholar Express Journal, 2021)
The article analyzes the role of Zaratustra in the development process of early countries in Central Asia. In addition, some statements about early cities in Central Asia, especially in Old Bactria and Margiona are highlighted in the article
Keywords: Kuzalikir; Aryanam Vayja; Old Bactria; Margiona